Environmental risks for children oral health in Low Danube region - Goncharov, V.; Velikov, M.; Schnayder, S.; Denga, O.; Maximenko, Y. (Journal of Education, Health and Sport, 2021)
The study was aimed to assess the environmental risks for children oral health in Low Danube region. Material and methods. The study was conducted in 2011-2021. Information on the state of drinking water, the level of environmental safety of food, qualitative and quantitative composition of food was obtained from the reports of territorial institutions of the sanitary-epidemiological service of Odessa region. Actual nutrition was assessed using standard questionnaires. The assessment of the level of environmental and hygienic safety was based on the recommendations of the EPA. Statistical processing was performed by methods of analysis of variance and correlation using specialized software Statistica 10.0. Results. Excessive carbohydrate intake and excessive nitrate load are the main environmental risk factors for dental pathology in children living in the Danube region. Qualitative composition of diets plays a bigger role than mineral composition of drinking water. Conclusion. 1. Drinking water of suboptimal mineral composition was consumed by 41.7% of people, high content of refined carbohydrates was inherent in the diets of 63.0% of surveyed children. 2. Children’s diet is characterized with subdeficiency of B vitamins, excessive consumption of refined carbohydrates and a significant nitrate load.